AGRICULTURE OF THE TRANS- CASPIAN REGION OF THE GENERAL- GUBERNATORIES OF TURKESTAN IN THE GERMAN RESEARCH (THE END OF THE 19TH CENTURY - THE BEGINNING OF THE XX CENTURY) - Elmurodovich, Rakhimov Bektosh (International Journal of Psychosocial Rehabilitation, 2020)
The cultural, economic, and political ties between the peoples of Central Asia and Western Europe have a long history. The interest of European explorers to Central Asia continued from the Middle Ages to the modern times. As a result, valuable scientific materials on the geography, history, ethnography of our country are collected. In addition to the English and French in the area, there were many Germanic people. German researchers traveled to the Turkestan region in the late 19th and early 20th centuries on the orders of the German Empire and the Russian Empire. Among them are naturalists, military topographers, officers, engineers, and orientalists and ethnographers. The commonality of these researchers is that they all received higher education and studied in Berlin, Würzburg, Göttingen, Jena, Magdeburg, Dresden and others. Almost all of the researchers left notes and memories of their travels. Among the researchers interested in Turkistan were representatives from various fields. The following is a summary of German developments based on the case study of the Turkestan governor-general in the Caspian region.As a result of the military invasion of the 1960s and 1960s, these territories were included in the system of legal, political and socio-economic relations that had been enforced by force. These relationships have undermined traditional relations in the region and their development opportunities on a national basis. There have been cases of land seizures belonging to indigenous people in providing land for specially evacuated by the Tsarist government, as well as arbitrary arrivals to Turkestan.After the conquest of Krasnovodsk and Mangyshlak by Tsarist Russia, the Caspian division was established (1874), which was then transferred to the Caucasus deputy. With the occupation of the Akhaltekin oasis in 1882 the department was given the status of a province. Later (1890-1897) the Caspian region was transferred directly to the Russian Ministry of Defense. The city of Ashgabat is the administrative center of the region. Administratively, the Caspian region is divided into the provinces of Ashgabat, Krasnovodsk, Mangyshlak, Merv and Tejen. The Turkestan governorship served as a huge raw material base in the economic life of the Russian Empire.The sale of cotton from Turkestan to Russia began in the 16th-17th centuries. In the second half of the eighteenth century, Asian cotton fiber was suppressed by Western European goods. Central Asian cotton, compressed by British cotton, has been of great importance to the Russian industry since the 50s of the 19th century.In Turkestan, cotton processing was practically occupied by women at home. Various fabrics, winter clothes, bedding and paper were made from cotton. German researcher A. Opel speaks about the history of cotton